Do Female Directors Manipulate Earnings? - Kontesa, Maria; Chai, Lee Sia; Brahmana, Rayenda Khresna; Contesa, Sisca (Jurnal Ilmiah Akuntansi dan Bisnis, 2020)
This study aims to examine the effect of female directors in firm’s earnings management for a sample of 263 Malaysian listed firms over 2013-2017 period. After running a robust panel regression, the result of this study shows that firm that have higher participation rate of women in the boardroom will have a higher tendency of manipulating earnings. The reason why there is a significant relationship between female directors and earnings management might be caused by the corporate culture pressure on women. The findings provide insight for industry and policymakers on the impact of gender diversity on earnings management. It may serve as a guideline in their selection of the organization's top management and decision-making process. Keywords: Female directors, earnings quality, women on board, earnings management.